Human Amniotic Fluid Mesenchymal Stem Cells Improve Ovarian Function During Physiological Aging by Resisting DNA Damage - Boxian Huang; Boxian Huang; Chenyue Ding; Qinyan Zou; Jiafeng Lu; Wei Wang; Hong Li (Frontiers Media S.A., 2020)
Many studies have shown that mesenchymal stem cells have the ability to restore function in models of premature ovarian insufficiency disease, but few studies have used stem cells in the treatment of ovarian physiologic aging (OPA). This experimental study was designed to determine whether human amniotic fluid mesenchymal stem cells (hAFMSCs) have the ability to recover ovarian vitality and to determine how they function in this process. Mice (12-14 months old) were used in this study, and young fertile female mice (3-5 months old) were the control group. Ovarian markers for four stages of folliculogenesis and DNA damage genes were tested by qPCR and western blot. hAFMSCs were used to treat an OPA mouse model, and the animals treated with hAFMSCs displayed better therapeutic activity in terms of the function of the mouse ovary, increasing follicle numbers and improving hormone levels. In addition, our results demonstrated that the marker expression level in ovarian granular cells from patients with OPA was elevated significantly after hAFMSC treatment. In addition, the proliferation activity was improved, and apoptosis was dramatically inhibited after hAFMSCs were cocultured with hGCs from OPA patients. Finally, in this study, hAFMSCs were shown to increase the mRNA and protein expression levels of ovarian markers at four stages of folliculogenesis and to inhibit the expression of DNA damage genes. These works have provided insight into the view that hAFMSCs play an integral role in resisting OPA. Moreover, our present study demonstrates that hAMSCs recover ovarian function in OPA by restoring the expression of DNA damage genes.